The rate of lactate removal after maximal exercise: the effect of intensity during active recovery - Riganas, C. S.; Papadopoulou, Z.; Psichas, N.; Skoufas, D.; Gissis, I.; Sampanis, M.; Paschalis, V.; Vrabas, I. S. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The aim of the present investigation was to determine the greater rate of lactate removal after a maximal rowing test using different intensities during active recovery.